Effect of Solid Properties on Axial Liquid Dispersion in Bubble Column - Ali Raad Mohammed Jawad (Al-Khwarizmi College of Engineering – University of Baghdad, 2012)
Experiments were conducted to study axial liquid dispersion coefficient in slurry bubble column of 0.15 m inside diameter and 1.6 m height using perforated plate gas distributor of 54 holes of a size equal to 1 mm diameter and with a 0.24 free area of holes to the cross sectional area of the column. The three phase system consists of air, water and PVC used as the solid phase. The effect of solid loading (0, 30 and 60 kg/m3) and solid diameter (0.7, 1.5 and 3 mm) on the axial liquid dispersion coefficient at different axial location (25, 50 and 75 cm) and superficial gas velocity covered homogeneous-heterogeneous flow regime (1-10 cm/s) were studied in the present work. The results show that the axial liquid dispersion coefficient increases with increasing superficial gas velocity, axial distance, solid concentration and an inverse relationship with particles diameter